Grants, Remittances, and the Equilibrium Real Exchange Rate in Sub-Saharan African Countries - Mongardini, Joannes; Rayner, Brett (Washington, D.C. : International Monetary Fund, 2009)
This paper builds on the methodology developed by Chudik and Mongardini (2007) to estimate the relationship between grants and remittances and the equilibrium real exchange rate in Sub-Saharan African (SSA) countries using panel techniques. The results indicate that grants and remittances are not associated, in the long run, with an appreciation of the real effective exchange in SSA and are therefore not likely to give rise to Dutch disease effects. These findings suggest that grants and remittances may be serving to ease supply constraints or boost productivity in the non-tradable sector in the recipient economies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Equilibrium Real Exchange Rate; Exchange Rate; Grant Inflow; Grant; WP; Tanzania, United Republic of